Human proteinase 3 resistance to inhibition extends to alpha‐2 macroglobulin. (24th February 2020) - N'Guessan, Koffi; Grzywa, Renata; Seren, Seda; Gabant, Guillaume; Juliano, Maria A.; Moniatte, Marc; van Dorsselaer, Alain; Bieth, Joseph G.; Kellenberger, Christine; Gauthier, Francis; Wysocka, Magdalena; Lesner, Adam; et al.
Abstract : Polymorphonuclear neutrophils contain at least four serine endopeptidases, namely neutrophil elastase (NE), proteinase 3 (PR3), cathepsin G (CatG), and NSP4, which contribute to the regulation of infection and of inflammatory processes. In physiological conditions, endogenous inhibitors including α2‐macroglobulin (α2‐M), serpins [α1‐proteinase inhibitor (α1‐PI)], monocyte neutrophil elastase inhibitor (MNEI), α1‐antichymotrypsin, and locally produced chelonianins (elafin, SLPI) control excessive proteolytic activity of neutrophilic serine proteinases. In contrast to human NE (hNE), hPR3 is weakly inhibited by α1‐PI and MNEI but not by SLPI. α2‐M is a large spectrum inhibitor that traps a variety of proteinases in response to cleavage(s) in its bait region. We report here that α2‐M was more rapidly processed by hNE than hPR3 or hCatG. This was confirmed by the observation that the association between α2‐M and hPR3 is governed by a k ass in the ≤ 10 5  m −1 ·s −1 range. Since α2‐M‐trapped proteinases retain peptidase activity, we first predicted the putative cleavage sites within the α2‐M bait region (residues 690–728) using kinetic and molecular modeling approaches. We then identified by mass spectrum analysis the cleavage sites of hPR3 in a synthetic peptide spanning the 39‐residue bait region of α2‐M (39pep‐α2‐M). Since the 39pep‐α2‐M peptide and the corresponding bait area in the whole protein do not contain sequences with a high probability of specific cleavage by hPR3 and were indeed only slowly cleaved by hPR3, it can be concluded that α2‐M is a poor inhibitor of hPR3. The resistance of hPR3 to inhibition by endogenous inhibitors explains at least in part its role in tissue injury during chronic inflammatory diseases and its well‐recognized function of major target autoantigen in granulomatosis with polyangiitis. Abstract : We characterized the neutralization of human proteinase 3 (hPR3) by α2‐macroglobulin (α2‐M) and identified the cleavage site of hPR3 in the 39‐residue bait region (39pep‐α2‐M) of α2‐M by mass spectrometry. α2‐M was slowly cleaved by hPR3. The presence of a P2 valine, leucine, or histidine made 39pep‐α2‐M peptide resistant to cleavage by hPR3. Altogether, with the whole‐protein sensitivity analysis, the results suggest that α2‐M is not an efficient inhibitor of hPR3.